High-Pressure Performance of Mixed-Conducting Oxygen Electrodes: Effect of Interstitial versus Vacancy Conductivity - Railsback, Justin; Hughes, Gareth; Mogni, Liliana Verónica; Montenegro Hernandez, Alejandra; Barnett, Scott (Electrochemical Society, 2016)
Fil: Railsback, Justin. Northwestern University; Estados Unidos